A statistical channel model for on body Area networks in Ultra Wide Band Communications (2009)
This paper presents a novel statistical channel model for Ultra Wide Band Communications when On Body Area Networks Environments are considered. Results and Analysis of frequency measurements from 1GHz to 12GHz for body area networks are described. We propose a modified Saleh-Valenzuela statistical channel model considering different assumptions for small scale statistics in the model. Results show that the small scale amplitude follows a log normal distribution, the inter arrival times between multi path components are poisson process; the decay factor, the number of paths and clusters follow exponential distributions. The proposed model can be used for realistic simulations for on body communications in Ultra Wide Band systems. © 2009 IEEE.